Incremental value of single photon emission tomography/computed tomography in 3-phase bone scintigraphy of an accessory navicular bone - Jain, Sachin (Medknow Publications & Media Pvt Ltd, 2014)
Accessory navicular bone is one of the supernumerary ossicles in the foot. Radiography is non diagnostic in symptomatic cases. Accessory navicular has been reported as a cause of foot pain and is usually associated with flat foot. Increased radio tracer uptake on bone scan is found to be more sensitive. We report a case highlighting the significance of single photon emission tomography/computed tomography in methylene diphosphonate bone scan in the evaluation of symptomatic accessory navicular bone where three phase bone scan is equivocal.